Probabilistic assessment of exposure to hair cosmetic products by the French population. (June 2016) - Ficheux, A.S.; Bernard, A.; Chevillotte, G.; Dornic, N.; Roudot, A.C.
Abstract: Cosmetic exposure data are limited in Europe and especially in France. The aim of this study was to assess the exposure to hair cosmetics using recent consumption data (percentage of users, frequency of use and amount per use) generated for the French population (Ficheux et al., 2015, 2016). Exposure was assessed using a probabilistic method for eleven hair products: liquid shampoo, dry shampoo, conditioner, hair mask, hair serum, hair oil, styling lacquer, styling gel, styling foam, styling wax and styling spray. Exposure was assessed by sex and by age classes in adults and children. Pregnant women were also studied. For liquid shampoo, conditioner and some styling products (gel, lacquer and foam), the levels of exposure were higher than the values currently used by the Scientific Committee on Consumer Safety (SCCS). Exposure values found for styling wax and styling spray were lower than SCCS values. Exposure was assessed for the first time for dry shampoo, hair mask, hair serum and hair oil products. These new French exposure values will be useful for safety assessors and for safety agencies in order to protect the general population and these at-risk populations. Highlights: The aim of the study was to assess the exposure to hair cosmetics in French consumers. Exposure was assessed using a probabilistic method for eleven hair products. Exposure was assessed by sex and by age classes in adults and children.